1997
DOI: 10.1046/j.1365-2141.1997.252670.x
|View full text |Cite
|
Sign up to set email alerts
|

Rarity of microsatellite genomic instability in B‐cell non‐Hodgkin's lymphomas in hepatitis C virus‐infected patients

Abstract: Summary. Several groups have emphasized the likely implication of the hepatitis C virus (HCV) in a fraction of B-cell nonHodgkin's lymphomas. Since only a minority of patients with HCV infection and monoclonal mixed cryoglobulinaemia develop overt lymphoma, the identification of predisposing factors has relevant clinical implications. The replication error phenotype (RER þ ), as revealed by widespread microsatellite instability, is caused by defects in DNA mismatch repair genes, and has been frequently disclos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The results of molecular studies fully support the concept of a true B cell malignancy when a clinically overt lymphoma develops. Further efforts are needed to identify the MC patients who will develop such overt malignancy (10,41), and diagnosis of bone marrow indolent lymphoma solely on pathologic grounds appears insufficient to this end. The integration of molecular analyses of B cell clonality with clinical and pathologic findings may be crucial to better elucidate this issue.…”
Section: Discussionmentioning
confidence: 99%
“…The results of molecular studies fully support the concept of a true B cell malignancy when a clinically overt lymphoma develops. Further efforts are needed to identify the MC patients who will develop such overt malignancy (10,41), and diagnosis of bone marrow indolent lymphoma solely on pathologic grounds appears insufficient to this end. The integration of molecular analyses of B cell clonality with clinical and pathologic findings may be crucial to better elucidate this issue.…”
Section: Discussionmentioning
confidence: 99%
“…50 In contrast with this finding, research into hepatitis C virus associated lymphoma has not shown microsatellite instability to be present. 48 The role of microsatellite instability in neoplastic transformation has been the subject of recent investigations. Microsatellite instability has been implicated as a pathogenetic mechanism in subsets of tumours linked pathogenically to chronic infection and inflammation, such as tumours occurring after schistosomiasis, viral hepatitis B, chronic ulcerative colitis, or papillomavirus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Hematological malignancies have been reported to display microsatellite instability (De Vita et al, 1997;Hayami et al, 1999;Kaneko et al, 1996;Kodera et al, 1999;Larson et al, 1997), but whether they are also deficient in MMR was still a matter of debate. To help resolve this issue, we studied MMR proficiency in several hematological cancer cell lines, using both biochemical and genetic analyses, and our results suggest that a significant portion of hematological cancer cells with MSI are MMR defective.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its demonstration in solid tumors, MSI has also been observed in hematological malignancies (De Vita et al, 1997;Hayami et al, 1999;Kaneko et al, 1996;Kodera et al, 1999;Larson et al, 1997). However, whether these hematological malignancies are associated with MMR defects is still controversial.…”
Section: Introductionmentioning
confidence: 99%